Diversity and Composition of Tree Species Regeneration in the Secondary Forests of Chittagong, Bangladesh - Newaz, MD. Shah (Indian Forester, 2006)
A regeneration survey was conducted in the tropical forests of Chittagong Division, which are considered to be in secondary forest state. A total of 84 sample plots (covering all the four aspects and three slope positions ie., hill foot, mid-hill and hilltop) of size 3m Ã— 3m were surveyed in terms of perennial tree species. A total of 290 individuals of 32 tree species were recorded from the sampled area representing 20 families and 25 genera. Maximum number of species (04) was recorded from the family Leguminosae followed by Moraceae and Myrtaceae with 03 species each. The average number of individuals per hectare was 3836, which were 5820, 2540, 3651 and 3333 in the south, north, east and western aspects, respectively. The figures for the valley, mid-hill and hilltop were 2262, 4444 and 4802, respectively. The total number of species was significantly higher in the southern aspect compared to other three aspects. Stereospermum chelonoides was found the dominating species representing 15.52% of the total individuals followed by Holarrhena antidysenterica (8.97%), Ficus auriculata (8.97%) and Albizia procera (7.93%). Stereospermum chelonoides had the highest (32.90) Importance Value Index followed by Ficus auriculata (21.44), Holarrhena antidysenterica (20.02), and Albizia procera (18.67). It was observed that in the southern and eastern aspects Stereospermum chelonoides is clearly dominating while northern aspect is dominated by Ficus auriculata. Again the top and mid-hill is dominated by Stereospermum chelonoides but the valley is dominated by Ficus auriculata.